2018
DOI: 10.1016/j.ebiom.2018.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Trial of Intrathecal Mesenchymal Stem Cell-derived Neural Progenitors in Progressive Multiple Sclerosis

Abstract: BackgroundMultiple sclerosis (MS) is an immune-mediated demyelinating disease of the central nervous system and is one of the leading causes of disability in young adults. Cell therapy is emerging as a therapeutic strategy to promote repair and regeneration in patients with disability associated with progressive MS.MethodsWe conducted a phase I open-label clinical trial investigating the safety and tolerability of autologous bone marrow mesenchymal stem cell-derived neural progenitor (MSC-NP) treatment in 20 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
118
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 140 publications
(124 citation statements)
references
References 41 publications
3
118
1
2
Order By: Relevance
“…Stem cell‐based therapies can greatly impact the field of regenerative medicine. MSCs have been used in preclinical and clinical studies to treat degenerative diseases, such as AD (Cui et al, ; Han et al, ; J. Shin et al, ; X. Wang, Ma, et al, ), DDD (Ahn et al, ; Beeravolu et al, ; Pereira et al, ; Perez‐Cruet et al, ), MS (Harris et al, ; Nasri et al, ; Planchon et al, ), PD (Jamali et al, ; H. Kim, Lee, et al, ), and RDD (Mead, Amaral, & Tomarev, ), as summarized in Table . The regenerative mechanisms of transplanted MSCs for these diseases are still unclear; however, some reports have suggested that MSCs have the potential to differentiate or have paracrine effects in vivo (Lee, Choi, Cha, & Hwang, ).…”
Section: Promising Applications Of Mscsmentioning
confidence: 99%
See 4 more Smart Citations
“…Stem cell‐based therapies can greatly impact the field of regenerative medicine. MSCs have been used in preclinical and clinical studies to treat degenerative diseases, such as AD (Cui et al, ; Han et al, ; J. Shin et al, ; X. Wang, Ma, et al, ), DDD (Ahn et al, ; Beeravolu et al, ; Pereira et al, ; Perez‐Cruet et al, ), MS (Harris et al, ; Nasri et al, ; Planchon et al, ), PD (Jamali et al, ; H. Kim, Lee, et al, ), and RDD (Mead, Amaral, & Tomarev, ), as summarized in Table . The regenerative mechanisms of transplanted MSCs for these diseases are still unclear; however, some reports have suggested that MSCs have the potential to differentiate or have paracrine effects in vivo (Lee, Choi, Cha, & Hwang, ).…”
Section: Promising Applications Of Mscsmentioning
confidence: 99%
“…These dopaminergic neuron cells survived when transplanted into a rat model of PD and displayed greater improvement of behavioral impairments (Y. Wang et al, ). In addition, MSCs have been investigated for the treatment of MS (Harris et al, ; Nasri et al, ; Planchon et al, ). Potential of the MSCs differentiated into neural progenitor cells was investigated to treat MS using a chronic experimental autoimmune encephalomyelitis (EAE) mouse model (Constantinescu, Farooqi, O'Brien, & Gran, ).…”
Section: Promising Applications Of Mscsmentioning
confidence: 99%
See 3 more Smart Citations